Thermal performance of shaded recessed wall facade of a cellular office space in Johor Bahru, Malaysia - Abdullahi, Muhammed Gambo (2020)
Direct solar insolation on unshaded facade causes severe overheating of the indoor environment in a tropical climate, and this would reduce the performance and efficiency of task carried out in the office. External shading strategies have been identified as one of the passive design strategies to mitigate indoor thermal effect in the tropics. As an option, additional design strategy such as recesses on facades, and shade buildings provide exterior projected shading devices. However, literature on studies related to on the recessed wall facade (RWF) are limited particularly in Malaysia. In this study, the influence of RWF on the indoor thermal conditions of an office space in Malaysia was investigated. Three RWF types (vertical, horizontal and punched-hole) recessed facade were investigated and compared with unshaded facade (UF). The thesis aims to investigate the potentials of applying RWF shading strategies to improve thermal performance by reducing the harsh indoor environmental conditions of office spaces in Johor Bahru, Malaysia. The research design employed an exploratory survey to identify RWF types in Malaysia. Further investigation was conducted using the integrated environmental solution-virtual environment (IES) simulation software. The results showed that deeper depth, punched-hole recessed façade type and RWF with insulation performed better with all the thermal parameters such as indoor air temperature, indoor relative humidity, indoor solar heat gain and indoor surface temperature. While the comparison evaluated between RWF types and exterior shading device (ESD) revealed the possibility of using RWF as an alternative to ESD. The findings revealed some effect of thermal performance of the RWF shading strategy on office space through the series of simulations. The results showed the shading strategies which provide a solar gain reduction ranging from 53.7% to 64.8%, invariably reduced the percentage of harsh indoor thermal conditions. Similarly, the minimum, maximum and average indoor air temperature reduction of 1.44 °C, 2.09°C and 1. 83 °C respectively were recorded. Surface temperature reduction was from 1.0% to 7.4% while the relative humidity was brought down and maintained AT a favourable mean value of not more than 55% within the comfort zone by horizontal recessed (HR) and punched-hole recessed (PHR). Therefore, these findings offer valuable information tool with RWF shading option to building sector stakeholders through various design models with various thermal performance levels.